Blood and Bone, Tears and Oil: Climate Change, Whaling, and Conflict in the Seventeenth-Century Arctic. Issue 1 (26th April 2022) - Degroot, Dagomar
Abstract: In the seventeenth century, the climate of the Arctic cooled, warmed briefly, and cooled again, just as European merchants established new industries to extract the region's resources. Few were larger or more violent than the whaling industry that exploited bowhead whales between Jan Mayen and Svalbard. This article argues that linked changes in climate and animal behavior influenced violence among whalers in different ways during three stages of the seventeenth-century industry. In the first, cooling discouraged violence by increasing the regional extent of sea ice, which led both whales and whalers to congregate in tight quarters, raising the cost of hostilities among whalers. In the second, violence provoked attempts to colonize fortified whaling stations year-round, leading to a shift in polar bear behavior and exposing overwintering whalers to some of the coldest weather of the Little Ice Age in the Arctic. In the third, sweeping changes in climate and whale culture helped doom whaling companies and their fortified whaling stations, while encouraging open-sea whaling that transformed where and how whalers could fight one another. This article reveals, above all, the potential of combining climate history with animal-human history to provide fresh perspectives on the past, present, and future.